2006
DOI: 10.1017/s0012162206000776
|View full text |Cite
|
Sign up to set email alerts
|

Medical, surgical, and health outcomes of gastrostomy feeding

Abstract: A prospective controlled study with repeated measures before and after surgery examined the medical, surgical, and health outcomes of gastrostomy for children with disabilities at a tertiary paediatric referral centre in the North Thames area, UK. Anthropometric measures included weight, mid-upperarm and head circumference. Five-day prospective food diaries were completed and data on physical health and surgical outcomes recorded. Seventy-six children participated and underwent gastrostomy (44 males, 32 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 29 publications
3
79
1
3
Order By: Relevance
“…Moreover, it is better to prepare families for some of the possible negative aspects of gastrostomy feeding as caregivers will have to learn new nursing procedures and there may be side-effects of surgery. 7 Not all anxiety about tube feeding is psychological, however, and parents may have concerns about incurring additional costs associated with tube feeding and its affordability, particularly where equipment and feeds are not provided as part of a health plan or health service. Here, financial advice may be necessary.…”
Section: Investments In Oral Feeding: Disability and Child Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it is better to prepare families for some of the possible negative aspects of gastrostomy feeding as caregivers will have to learn new nursing procedures and there may be side-effects of surgery. 7 Not all anxiety about tube feeding is psychological, however, and parents may have concerns about incurring additional costs associated with tube feeding and its affordability, particularly where equipment and feeds are not provided as part of a health plan or health service. Here, financial advice may be necessary.…”
Section: Investments In Oral Feeding: Disability and Child Developmentmentioning
confidence: 99%
“…The demands of care can be high in this population of children as they are frequently ill and require numerous visits to health professionals and periods of hospitalization. 7 Frequent hospital appointments, because of the complexity of children's needs, and the lack of integrated services, in some cases, can also create additional demands on children and their caregivers, pointing to the importance of the role of key workers in coordinating children's care. 8 Research into the benefits of gastrostomy tube feeding reports improvements in health and weight gain 7,9 and decreased stress, as experienced by caregivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilise a study of professional and parental interactions that occurred at specific points in the patient referral pathway during the course of a research study evaluating the effectiveness of gastrostomy feeding interventions coordinated by one of the authors (reported in Craig et al 2006). We draw on observations of clinical consultations following a referral for gastrostomy and referral letters in patients' notes, in addition to interviews with parents (reported in Craig 2004;Craig, Scambler & Spitz 2003).…”
Section: Research Contextmentioning
confidence: 99%
“…Gastrostomy feeding has been found to improve weight and mid-arm circumference (Cook et al, 2005;Sullivan et al, 2005;Craig et al, 2006;Ramelli et al, 2007), reduce feeding time (Cook et al, 2005;Sullivan et al, 2005), improve the quality of life of caregivers and children (Sullivan et al, 2004;Cook et al, 2005;Kindermann et al, 2008;Mahant et al, 2009), and result in other health gains (Sullivan et al, 2005). The prospect of gastrostomy feeding, however, is seen as a major intervention by parents and therefore detailed preparation and discussion are needed.…”
Section: Routes Of Deliverymentioning
confidence: 99%